Mixed Depression in the Post-COVID-19 Syndrome: Correlation between Excitatory Symptoms in Depression and Physical Burden after COVID-19 - Alessio Simonetti; Evelina Bernardi; Stella Margoni; Antonello Catinari; Antonio Restaino; Valentina Ieritano; Marta Palazzetti; Federico Mastrantonio; Delfina Janiri; Matteo Tosato; Francesco Landi; Gabriele Sani (Brain Sciences, 2023)
The relationship between depression and post-COVID-19 disease syndrome (post-COVID-19 syndrome) is established. Nevertheless, few studies have investigated the association between post-COVID-19 syndrome and mixed depression, i.e., a specific sub-form of depression characterized by high level of excitatory symptoms. Aims of the present study are: (a) to compare the post-COVID-19 syndrome’s burden in depressed and non-depressed patients, and (b) to investigate the correlation between post-COVID-19 syndrome’s burden and the severity of mixed depression. One thousand and forty six (n = 1460) subjects with post-COVID-19 syndrome were assessed. Subjects were divided into those with (DEP) or without (CONT) depression. Sociodemographically, post-COVID-19 syndrome’s symptoms number and type were compared. In DEP, association between levels of excitatory symptoms and the presence of post-COVID-19 syndrome’s symptoms were additionally assessed. DEP showed greater percentages of family history of psychiatric disorders than CONT. DEP showed higher percentages of post-COVID-19 symptoms than CONT. A greater level of excitatory symptoms were associated to higher frequencies of post-COVID-19 syndrome’ symptoms. Higher levels of post-COVID-19 syndrome’s symptoms in DEP corroborate the evidence of a common pathway between these two syndromes. Presence of excitatory symptoms seem to additionally add a greater illness burden. Such findings might help clinicians choose the appropriate treatment for such states. More specifically, therapies aimed to treat excitatory symptoms, such as antipsychotics and mood stabilizers, might help reduce the illness burden in post-COVID-19 patients with mixed depression.